Implementasi Pembelajaran Berbasis Proyek Claymation berbantuan Artificial Intelligence untuk Meningkatkan Literasi Digital Mahasiswa - Firdiawan Ekaputra (Pedagogika: Jurnal Ilmu-Ilmu Kependidikan, 2026)
Digital literacy has become an essential competency for prospective teachers in response to the rapid advancement of educational technology and the integration of Artificial Intelligence (AI) into higher education. This study investigates whether AI-integrated Project-Based Learning (PBL) using claymation media significantly enhances students’ digital literacy in the Chemistry Multimedia Learning course. A quantitative approach was employed using a pre-experimental method with a One-Group Pretest–Posttest Design. The participants consisted of Chemistry Education students at Universitas Jambi enrolled in the Chemistry Multimedia Learning course during the 2025/2026 academic year. Data were collected through a digital literacy questionnaire and analyzed using the Shapiro–Wilk normality test and a paired-sample t-test. The findings revealed that the students’ mean digital literacy score increased from 71.86 in the pretest to 87.14 in the posttest. The normality test confirmed that the data were normally distributed, while the paired-sample t-test demonstrated a statistically significant improvement following the implementation of AI-integrated claymation-based PBL. These findings indicate that integrating AI into claymation-based PBL provides an effective pedagogical strategy for strengthening university students’ digital literacy and supporting technology-enhanced learning in chemistry education.